1998
DOI: 10.1046/j.1526-4610.1998.3806465.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and Migraine: Increase of IL‐5 and IL‐4 Plasma Levels

Abstract: Thirty-two patients suffering from migraine without aura were assessed during in interictal period to evaluate the contribution of cytokines to the pathophysiology of migraine. To this end, plasma levels of IFN-gamma, IL-4, IL-5, and IL-10 were measured by enzyme-linked immunosorbent assay (ELISA) techniques. Plasma levels of both IFN-gamma and IL-10 were not increased in the patients and did not differ significantly from healthy controls. Of interest, we observed a strong increase of IL-5 levels in 84.3% as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 0 publications
2
55
0
Order By: Relevance
“…The role of PGR has been reported in migraine [Colson et al, 2005] and more recently in migraine associated vertigo syndrome [Lee et al, 2007]. Cytokines are part of the acute and chronic inflammatory responses of the central nervous system [Moore et al, 1980;Munno et al, 1998]. TNFa is a proinflammatory cytokine that has been shown to play a role in nociception [Sachs et al, 2002;Wagner and Myers, 1996].…”
Section: Other Genesmentioning
confidence: 99%
“…The role of PGR has been reported in migraine [Colson et al, 2005] and more recently in migraine associated vertigo syndrome [Lee et al, 2007]. Cytokines are part of the acute and chronic inflammatory responses of the central nervous system [Moore et al, 1980;Munno et al, 1998]. TNFa is a proinflammatory cytokine that has been shown to play a role in nociception [Sachs et al, 2002;Wagner and Myers, 1996].…”
Section: Other Genesmentioning
confidence: 99%
“…Thus, cytokine expression patterns have been used to distinguish normal and altered cell functions in a variety of clinical conditions. In the past, conflicting results have been reported regarding the peripheral cytokine secretion pattern in migraine [14][15][16], suggesting that different routes are involved in the generation of migraine pain. In the present study, we investigated the NOS-2/COX-2 network and its possible influence on Th1/Th2 balance and cytokine production.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Conflicting findings are also available regarding adhesion molecules in migraineurs. One such study showed a marked decrease in expression of intercellular adhesion molecule (ICAM)-1 and soluble (s)ICAM-1, and reduced levels of IL-4 in serum during spontaneous and nitric oxide (NO)-induced migraine attacks.…”
mentioning
confidence: 99%